Chloroplast Translation: Structural and Functional Organization, Operational Control, and Regulation. Issue 4 (2nd April 2018) - Zoschke, Reimo; Bock, Ralph
Abstract: Chloroplast translation is essential for cellular viability and plant development. Its positioning at the intersection of organellar RNA and protein metabolism makes it a unique point for the regulation of gene expression in response to internal and external cues. Recently obtained high-resolution structures of plastid ribosomes, the development of approaches allowing genome-wide analyses of chloroplast translation (i.e., ribosome profiling), and the discovery of RNA binding proteins involved in the control of translational activity have greatly increased our understanding of the chloroplast translation process and its regulation. In this review, we provide an overview of the current knowledge of the chloroplast translation machinery, its structure, organization, and function. In addition, we summarize the techniques that are currently available to study chloroplast translation and describe how translational activity is controlled and which cis -elements and trans -factors are involved. Finally, we discuss how translational control contributes to the regulation of chloroplast gene expression in response to developmental, environmental, and physiological cues. We also illustrate the commonalities and the differences between the chloroplast and bacterial translation machineries and the mechanisms of protein biosynthesis in these two prokaryotic systems.